Inhibited CSF1R Alleviates Ischemia Injury via Inhibition of Microglia M1 Polarization and NLRP3 Pathway - Xiaoxue Du; Yuzhen Xu; Shijia Chen; Marong Fang (Neural Plasticity)
Ischemia cerebral stroke is one of the common neurological diseases with severe inflammatory response and neuron death. The inhibition of colony-stimulating factor 1 receptor (CSF1R) which especially expressed in microglia/macrophage exerted neuroprotection in stroke. However, the underlying neuroinflammatory regulation effects of CSF1R in ischemia stroke are not clear. In this study, cerebral ischemia stroke mice model was established. The C57/B6J mice were administered with Ki20227, a CSF1R inhibitor, by gavage for 7 consecutive days (0.002 mg/kg/day) before modeling. The Rota-Rod test and neurobehavioral score test were investigated to assess neurobehavioral functions. The area of infarction was assessed by 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. The mRNA expressions of M1/M2 microglia markers were evaluated by real-time PCR. Immunofluorescence and Western blot were utilized to detect the changes of Iba1 and NLRP3 pathway proteins. Results showed that neurobehavioral function improvement was demonstrated by an increased stay time on the Rota-Rod test and a decreased neurobehavioral score in the Ki20227 treatment group. The area of infarction reduced in Ki20227 group when compared to the stroke group. Moreover, the mRNA expression of M1 microglia markers (TNF-α and iNOS) decreased while M2 microglia markers (IL-10 and Arg-1) increased. Meanwhile, compared to the stroke and stroke+PBS group, Ki20227 administration downregulated the expression of NLRP3, active caspase 1, and NF-κB protein in the ischemia penumbra of Ki20227 treatment group mice. In short, the CSF1R inhibitor, Ki20227, played vital neuroprotective roles in ischemia cerebral stroke mice, and the mechanisms may be via inhibiting microglia M1 polarization and NLRP3 inflammasome pathway activation. Our study provides a potential new target for the treatment of ischemic stroke injury.